Myocardial fibre calcification. Issue 10 (October 1981) - McClure, J; Pieterse, A S; Pounder, D J; Smith, P S
Abstract : Three cases of myocardial fibre calcification found at post-mortem examination are described. In one case there was antemortem hypercalcaemia and hyperphosphataemia and the case was clearly an example of metastatic calcification. In the other two cases there was ischaemic myocardial necrosis and calcification was seen in fibres which were not overtly necrotic, but which were both in proximity to (the majority) and remote from the necrotic zones. Since renal failure with hyperphosphataemia was present in both cases, these were considered to be examples of augmented (by the hyperphosphataemia) dystrophic calcification. The histological, histochemical and ultrastructural features were identical in the three cases. Hydroxyapatite formation was observed initially in mitochondria, followed by spillage of crystals into the cytosol and ultimately into the interstitium. It is suggested that the fundamental lesion is a dysfunction of the fibre membrane; the similarity of this reaction with the calcification seen in skeletal muscle fibres in various myopathies is noted and a unifying hypothesis of the mechanism of skeletal and cardiac muscle fibre calcification is thereby suggested.